The variability of lower third molar development in Northeast Malaysian population with application to age estimation - Johan, N.A.; Khamis, M.F.; Abdul Jamal, N.Sk.; Ahmad, B.; Mahanani, E.S. (The Journal of Forensic Odonto-Stomatology - JFOS, 2023)
This study aimed to assess the variability of the lower third molar (tooth 38 and 48) development in Northeast Malaysian population with respect to the side of dentition, to generate age prediction models and to compare the outcome with other studies. A total of 1080 orthopantomograms of Northeast Malaysian population aged between 14 and 25 years (540 males and 540 females) from the Hospital Universiti Sains Malaysia’s archive which met the inclusion and exclusion criteria were selected and the maturity stages of toothth 38 and 48 were scored using Demirjian’s stages (A-H). The findings showed a wide variation of the development of lower third molars in the Northeast Malaysian population. The roots developed earlier in males than in females. The development of the dentition on opposite sides of the mandible was synchronously in females and males. A multiple regression analysis shows that 71.1% of variance in age was explained by sex and developmental stage of tooth 48. An age prediction model was generated from the regression analysis: [Age = 7.117 + 1.907*(stage of tooth 48) – 0.432*(sex)] with mean prediction errors between -0.17 to 3.14 years. The obtained data in the current study are useful for references and determining age of unidentified human remains for identification investigation.